2001
DOI: 10.1021/ja010446v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Pressure Effects on Hydrophobic Interactions

Abstract: We report results on the pressure effects on hydrophobic interactions obtained from molecular dynamics simulations of aqueous solutions of methanes in water. A wide range of pressures that is relevant to pressure denaturation of proteins is investigated. The characteristic features of water-mediated interactions between hydrophobic solutes are found to be pressure-dependent. In particular, with increasing pressure we find that (1) the solvent-separated configurations in the solute-solute potential of mean forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
175
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(196 citation statements)
references
References 49 publications
19
175
2
Order By: Relevance
“…At fixed pressures it reaches its maximum, temperature of which is what we call T 2 , and then turns to decrease with increasing T; at fixed temperatures ͑below 350 K͒ it increases with increasing P, and the characteristic temperature T 2 decreases with increasing P. We note that W(1)/kT represents the solventmediated potential of mean force at the shortest possible distance in this model but may not correspond to the one at a contact pair in a real system; computer simulations of methane in water show that strength of solvent-mediated attraction increases with increasing pressure at solvent-separated configurations and at distances shorter than a crossover point around 3.9 Å. 20 The two characteristic temperatures, T 1 and T 2 , versus P are plotted in Fig. 8.…”
Section: Hydrophobic Hydration and Hydrophobic Attractionmentioning
confidence: 86%
See 2 more Smart Citations
“…At fixed pressures it reaches its maximum, temperature of which is what we call T 2 , and then turns to decrease with increasing T; at fixed temperatures ͑below 350 K͒ it increases with increasing P, and the characteristic temperature T 2 decreases with increasing P. We note that W(1)/kT represents the solventmediated potential of mean force at the shortest possible distance in this model but may not correspond to the one at a contact pair in a real system; computer simulations of methane in water show that strength of solvent-mediated attraction increases with increasing pressure at solvent-separated configurations and at distances shorter than a crossover point around 3.9 Å. 20 The two characteristic temperatures, T 1 and T 2 , versus P are plotted in Fig. 8.…”
Section: Hydrophobic Hydration and Hydrophobic Attractionmentioning
confidence: 86%
“…It is plotted in Fig. 7 as a function of T at the six pressures Pϭ0.1, 10,20,30,40, and 50 MPa. The strength of attraction as measured by ϪW(1)/kT shows dependences on temperature and on pressure similar to those of ex /kT.…”
Section: Hydrophobic Hydration and Hydrophobic Attractionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, with increasing temperature the association of hydrophobic particles is found to be enhanced in order to minimise the solvation entropy penalty [8,9]. This entropy-driven association process is usually referred to as hydrophobic interaction and has been subject of numerous simulation studies [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. * dietmar.paschek@udo.edu; http://ganter.chemie.uni-dortmund.de/~pas/ Hydrophobic effects are considered to play an important role concerning protein stability and other self assembly phenomena [4,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they are seen as an important driving force with regard to the folding of proteins [4,5,6]. Consequently, a wealth of studies of hydrophobic interactions using molecular simulation techniques have been undertaken over the past three decades [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Simulation studies have revealed that the contact state of a pair of hydrophobic particles in aqueous solution is entropically stabilized at ambient conditions [10,11].…”
Section: Introductionmentioning
confidence: 99%